Key Applications of AI Question-Answering Systems: Research and Technical Analysis Based on Game Text and Dialogue - Wu, Qineng (Transactions on Computer Science and Intelligent Systems Research, 2025)
With the rapid development of the global gaming industry, artificial intelligence (AI) applications in games have garnered increasing attention. In role-playing and open-world games, particularly, the intelligence of non-Player Characters’ (NPCs) dialogue systems is critical to enhancing player experience and interactivity. This paper investigates the applications of AI question-answering (QA) systems in gaming contexts by analyzing mainstream algorithms and models, their implementation workflows, advantages, and limitations. Additionally, it explores the challenges and future directions for AI-driven QA systems. The findings demonstrate that AI QA systems significantly improve game immersion and interactivity, particularly in dynamic dialogue generation and personalized narrative design. However, computational resource constraints and real-time performance remain major challenges. Future research should focus on reducing computational overhead, improving semantic accuracy, and enabling flexible adaptation of AI QA systems across diverse game genres. This study provides innovative insights for game developers and offers implications for extending AI applications to other domains.